2011
DOI: 10.1177/0269215510389200
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of community-based ambulation training for walking function of post-stroke hemiparesis: a randomized controlled pilot trial

Abstract: The findings demonstrate that community-based ambulation training can be helpful in improving walking ability of patients with post-stroke hemiparesis and may be used as a practical adjunct to routine rehabilitation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 26 publications
1
69
0
Order By: Relevance
“…In the community walking training, environmental dimensions are an important factor determining the level of community walking (Shumway-Cook et al 2002Park et al 2011). Thus, we believe that active participation and voluntary movement during various real community environmental situations improved walking function.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In the community walking training, environmental dimensions are an important factor determining the level of community walking (Shumway-Cook et al 2002Park et al 2011). Thus, we believe that active participation and voluntary movement during various real community environmental situations improved walking function.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, Park et al (2011) demonstrated that four weeks of community-based ambulation training consisting of various community situations helped improve walking ability of stroke patients. In addition, Stuart et al (2009) reported that community-based physical therapy involving environmental options was effective for improving ambulation in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations